Dynamic three-dimensional finite element analysis of orbital trauma - Moura, L. B. [UNESP]; Jürgens, P. C.; Gabrielli, M. A.C. [UNESP]; Pereira Filho, V. A. [UNESP] (Elsevier, 2021)
This study comprises a dynamic finite element (FE) analysis of the mechanisms of orbital trauma, specifically buckling and hydraulic theories. A digital model of the orbital cavity - including the eyeball, fatty tissue, extraocular muscles, and the bone orbit – was created from magnetic resonance imaging and computed tomographic data from a real patient. An impactor hit the FE model following two scenarios: one was a hydraulic mechanism for direct impact to the eyeball and the other a buckling mechanism for direct impact over the infraorbital rim. The first principal stress was calculated to determine the stress distribution over the orbital walls. The FE model presented more than 900,000 elements and time of simulation was 4.8 milliseconds (ms) and 0.6 ms, for the hydraulic and buckling mechanisms, respectively. The stress distribution in the hydraulic mechanism affected mainly the medial wall with a high stress area of 99.08 mm2, while the buckling mechanism showed a high stress area of 378.70 mm2 in the orbital floor. The presence of soft tissue absorbed the energy, especially in the hydraulic mechanism. In conclusion, the applied method of segmentation allowed the construction of a complete orbital model. Both mechanisms presented results that were similar to classic experiments. However, the soft tissue in the hydraulic mechanism absorbed the impact, demonstrating its role in orbital pathophysiology.
Keywords: Finite Element Analysis; Orbit; Orbital fractures